2017
DOI: 10.1155/2017/8486451
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the Influence of Health Insurance Status on Peoples’ Health Seeking Behaviour in Rural Ghana

Abstract: This paper examines the influence of health insurance status on healthcare use in rural Ghana using 286 sampled respondents from four rural communities in the Bekwai Municipality. Data were obtained using structured interview and Pearson's Chi square and bivariate regressions were used to analyse data. The results show low healthcare utilization among study participants, with most respondents having irregular use (43.5%) or rare use (43.3%). Respondents with health insurance utilized healthcare more than those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 20 publications
3
17
1
Order By: Relevance
“…Similar finding was reported by the study done in India on comprehensive health insurance program [14]. Similarly findings from our study was consistent with the results of other studies conducted in different types of health insurance program in Ghana, Republic Korea and Chhattisgarh, India [15,16,17].…”
Section: Health Service Utilizationsupporting
confidence: 93%
See 1 more Smart Citation
“…Similar finding was reported by the study done in India on comprehensive health insurance program [14]. Similarly findings from our study was consistent with the results of other studies conducted in different types of health insurance program in Ghana, Republic Korea and Chhattisgarh, India [15,16,17].…”
Section: Health Service Utilizationsupporting
confidence: 93%
“…Ethnicity, family occupation, perceived health status of family and wealth status also had significant role in health service utilization among overall households. Similar study conducted in Ghana reported that educational status and monthly income were major determinants of health service utilization among overall study group [15]. The study conducted in Republic Korea reflects educational status and household wealth status had also significant difference in health service utilization [16].…”
Section: Health Service Utilizationmentioning
confidence: 52%
“…29,30 In terms of healthcare-seeking behavior, people who are registered in the scheme use healthcare services more than those who are not insured. [30][31][32][33] Though the NHIS increased access to healthcare, this access is far from universal, as it demands premium payment before one can access healthcare. Many studies 8,-32,-34-36 reported varying proportions of the population who are not covered by the scheme; a World Bank study 7 reported that only 40% of the Ghanaian population were enrolled in the scheme by 2013.…”
Section: Coveragementioning
confidence: 99%
“…Therefore, all means to ensure good health, which includes the provision and use of health-care services, including maternal health services thus emerges as an important public health and policy issue and a matter of concern to stakeholders. This reflects in efforts to improve health outcomes and to meet international obligations to make health care broadly accessible [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%